AN OVERVIEW OF PLASTIC WASTE RECYCLING IN THE URBAN AREAS OF JAVA ISLAND IN INDONESIA - Darus, Nurdiana; Tamimi, Maya; Tirawaty, Silvi; Muchtazar, Muchtazar; Trisyanti, Dini; Akib, Rangga; Condorini, Dyota; Ranggi, Khair (UI Scholars Hub, 2020)
Plastic products have been an integral part of human lives. However, concerns over plastic pollution have been growing. Thus, alternative practices that allow more sustainable production and consumption pattern are urgently needed. Improving plastic recycling management is one of the solutions to prevent an increase in plastic pollution. This paper aims to uncover the potential of plastic recycling, to define factors that can leverage the expansion of the recycling process, and to evaluate possible measures that can realize such expansion, especially given the limited literature on these topics. Therefore, a four-month study, which involved two months of rigorous primary survey and interview and secondary data collection process to obtain valuable and accountable raw data, was conducted between October 2019–January 2020. The conducted study showed that the urban population in Java Island generated around 189,349 t of plastic waste per month, but only 11.83% of it was collected. The remaining 88.17% was either directly transported to landfills or littered in the environment. Five major plastic types were collected in the recycling stream, namely, rigid PP (25%), film HDPE (20%), rigid PET (20%), rigid HDPE (14%), and film PP (9%) with more than 80% of collected plastic waste originating from waste pickers. The paper highlights the major challenges in improving post-consumer recycling: (i) failure of post-consumer plastic recyclable to meet the quality industrial standard; (ii) limited recycling processes and infrastructure; (iii) low market demand for recycled products.